Use of rate of force development in field testing of ice-hockey players - Krajnák, J.; Kumstát, M. (Studia Sportiva, 2023)
Introduction: Ice hockey is a power-speed sport played on ice. The surface specification is very different from a normal surface, so it is important to look for the most appropriate measurements and specific off-ice tests that would better define ice-hockey performance. Therefore, the main purpose of this research was to determine the relationship of rate of force development (RFD) in back squat with commonly used off-ice and on-ice tests.